Welfare and Competition : A Simulation Approach - Rodriguez Castelan, Carlos (World Bank, Washington, DC, 2020)
This note focuses on the welfare and competition (WELCOM) microsimulation tool. WELCOM, an easy-to-use stata-based package with minimum data requirements, was conceived as part of larger World Bank efforts to better understand how competition policy can improve market efficiency and reduce poverty, especially in developing countries. Using examples from Mexico and Ethiopia in the telecommunications and food sectors, this note shows how WELCOM can estimate likely distributional effects - that is, decrease in price and poverty, and increase in product uptake - from expanding competition.